Language in Use : Cognitive and Discourse Perspectives on Language and Language Learning - Tyler, Andrea (Georgetown University round table on languages and linguistics series (2004), 2005)
"This book explores how language is shaped by the nature of human cognition and social-cultural activity, by studying how language is used in context in interactions between at least two people in order to achieve some purpose. It brings together perspectives from cognitive linguistics, discourse analysis, and first and second language acquisition research"--Provided by the publisher.